2009
DOI: 10.14429/dsj.59.1546
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in the Flow over Projectile with Wrap-around Fins

Abstract: This paper presents the results of a numerical study to understand the flow field over a projectile with wraparound fins. This investigation is performed in order to determine aerodynamic coefficients for the missile model for varying Mach number from 1.2 to 2.5. The roll moment coefficients were computed from the flow field solution and compared with other computational models and experimental works. The results show a reversal of the rolling moment in a Mach number from 1.2 to 1.4. While generating Mach numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These computed values of rolling moment coefficients of the fins also show a similar trend when compared with previous computational and experimental researches, which will be covered later in the validation section of this paper. The previous CFD simulations had failed to accurately compute this critical Roll reversal Mach number near Mach number ~1.0M (as proven experimentally) (Predicted range varied from ~1.0M to 1.8M) (Krishna et al 2009). In the current computation of single wrap-around fin it was successfully determined at ~1.2M.…”
Section: Comparison Of Computed Shock Structures Surface Pressures Andmentioning
confidence: 91%
See 1 more Smart Citation
“…These computed values of rolling moment coefficients of the fins also show a similar trend when compared with previous computational and experimental researches, which will be covered later in the validation section of this paper. The previous CFD simulations had failed to accurately compute this critical Roll reversal Mach number near Mach number ~1.0M (as proven experimentally) (Predicted range varied from ~1.0M to 1.8M) (Krishna et al 2009). In the current computation of single wrap-around fin it was successfully determined at ~1.2M.…”
Section: Comparison Of Computed Shock Structures Surface Pressures Andmentioning
confidence: 91%
“…The fin drag comparison, between the planar and the wrap-around, showed that the WAFs had 10% higher value as that of the planar fins. In the past, numerous numerical studies (Bagheri, Pasandidehfard, & Tavakoli Sabour 2018;Li, Abbas, & Rui, 2015;Krishna, Surit, Kushari, & Ghosh, 2009;Eidell, Nance, McGowan, Carpenter, & Moore, 2012;Murman, 2007) have been performed on planar and wrap-around finned missiles which have used inviscid, viscid and turbulent flow conditions. However, most of these studies were performed on a complete missile body with four fins, these studies form the basis of implying turbulence modelling to the current model.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, they showed that the sitting angle of the fins influences the rolling and lateral moments significantly, while it imposes minor effects onto pitching moment. Krishna et al 10 considered viscous and nonviscous flows around a rocket with CWAFs. They recognized the change in flow regime from subsonic to supersonic near the fin tips as the main factor contributing to the change in rotation direction at Mach numbers greater than 1.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide additional information for missile designers, a parametric study on wrap-around-fin missile configurations is conducted so as to determine their static aerodynamic characteristics at supersonic speed. [14][15][16][17][18][19][20][21][22][23] Our previous studies only focus on the qualitative and quantitative analysis for different Wrap-around fins (N ¼ 4, 6 and 8) by drawing the orthogonal tables for different parameters. 24 The current research will mainly focus on the characteristics comparisons between the flat fins and WAFs.…”
Section: Introductionmentioning
confidence: 99%